MODIFIKASI MEMBRAN POLYETHERSULFONE (PES) MENGGUNAKAN PELARUT NORMAL METHYL PYROLYDONE (NMP) SECARA NON-SOLVENT INDUCE PHASE SEPARATION (NIPS) - Umi Fathanah; Izarul Machdar; Medyan Riza; Nasrul Arahman; Mirna Rahmah Lubis; Mukramah Mukramah (Prosiding Seminar Nasional USM, 2019)
Clean water is a natural resource which is indispensable, due to the increase of population, water demand is also increasing. so that technology is needed in water treatment to satisfy the needs of clean water. Membrane separation technology is a technology that has grown rapidly in addressing the problems of water treatment. The purpose of this study was to determine the characteristics and performance of Polyethersulfone (PES) membranes modified with magnesium hydroxide or Mg(OH)2 and modification using chitosan. Membrane preparation was carried out by the phase inversion method, using an 18 wt% PES polymer modified with the addition of 0.2 wt% of Mg(OH)2, and modification using 0.2 wt% of chitosan. Furthermore, it was dissolved in N-Methyl pyrrolidone (NMP) as a solvent and the dope solution was stirred for 24 hours until it was homogeneous. Membrane characterization includes functional group analysis and measurement of the membrane water contact angle. Whereas membrane performance testing is done through permeability measurement and membrane rejection using a dead end ultrafiltration module. The results showed that the hydroxyl group (-OH) contained in Mg(OH)2 and chitosan were able to improve the hydrophilicity of the PES membrane. The membrane permeability coefficient modified with Mg(OH)2 gives a value of 8.236 L/m2.h.bar, while modifying the membrane using chitosan produces a value of 6.237 L/m2.h.bar. Both of them experience an increase compared to pure PES membrane without modification that has a permeability value of 4.123 L/m2.h.bar.